Alfa-Miforcal Project: the contribuition of the theory of social representations for the study of virtual learning communities - Testa Braz da Silva, Alcina Maria (Formazione & insegnamento, 2015)
Considering Education in this transformation context, it’s necessary to turn our eyes to man’s relations with this reality that now also includes the virtual. ALFA-MIFORCAL project advances toward this goal when it opens space for an investigation of the elements and relationships of meanings that defines a formation with quality. The virtual communities consist of interaction spaces, built from interests, knowledge and mutual projects (Lévy, 2000) e are characterized by a cooperation and exchange process that doesn’t rely on geographical proximity and instructional bonds. The construction of knowledge of a group that share objectives with the purpose of creating new meanings defines the concept of collaborative learning (Kaye, 1991). So, talking about virtual learning communities implies considering these meanings built in a shared way and spread in the process of interaction. A viable and promising path for the investigation of this scenario is indicated by the methodological-theoretical perspective of social representations, according to Moscovici (1978, 1981, 1984, 1986, 1988, 2003), which refers to a process of composition of knowledge that belongs to a social group and to the products of that process. This knowledge that is built is made of production and negotiation of meanings. The purpose of this work includes discussing the contribution that the theory of social representations may give to the analysis of the multiple objects of conversation that are created by the interaction between the participants of the virtual learning communities in context of the process of teacher formation, based on the proposal of the ALFA-MIFORCAL Project.